Correlation between eccentric training and functional tests in subjects with reconstructed ACL - Santos, Heleodório Honorato (2018)
Introduction: Eccentric training and jump tests are widely used to recover and measure deficits in knee strength and functionality after anterior cruciate ligament (ACL) reconstruction. Objective: To correlate knee extension and flexion torque generated by eccentric isokinetic training, with functional jump tests in subjects with reconstructed ACL. Method: Sixteen men with unilateral ACL reconstruction were assessed before and after 12 weeks of eccentric isokinetic training of knee flexors and extensors (3x10 MVC, 2x/week) at 30o/s for extension and flexion torque (isometric; concentric and eccentric at 30 and 120o/s) and functional jump tests (single, triple, cross and figure of 8). Inter- and intra-limb pre- and post-training mean peak torque (MPT), distance and jump test times were compared along with the correlations between these variables, considering P≤0.05. Results: The affected limb (AL) showed significant gain of extension and flexion torque (P<0.01) in the different test categories and velocities evaluated. In the non-affected limb (NAL), this only occurred in the eccentric category (30 and 120o/s), in the extension (P<0.01) and flexion (P<0.05 and P<0.01) torques, respectively. In the jumps, there was an increase in distance (single and triple; P<0.05) and a decrease in time (crossed and figure of 8; P<0.01), however, MPT x Jump correlations were weak (r<0.3) in the pre and post-training period in both limbs. Conclusion: Despite the gain in knee extension and flexion torque and jumping performance, the expected correlation was not satisfactory, suggesting that knee functionality involves other variables inherent to motor control. Level of Evidence IV; Type of study: Case series.